Characterisation of Acinetobacter with special reference to carbapenem resistance and biofilm formation - Dr. Amrita Pattanaik; Dr. Banashankari G.S. (Tropical Journal of Pathology and Microbiology, 2019)
Background: Acinetobacter species cause hospital outbreaks and are often multidrug resistant. A wide range of resistance determinants make them successful nosocomial pathogens. In the present study, authors have identified and speciated Acinetobacter from various clinical specimens by a simplified phenotypic identification scheme determined their antibiotic susceptibility pattern focussing on Carbapenem resistance and have also evaluated their biofilm producing ability.Method: Clinical samples were screened for Acinetobacter species and isolates were speciated. Antibiogram was determined by performing Kirby-Bauer disc diffusion method. Isolates resistant to Carbapenems were subjected to Modified Hodge Test (MHT) and Meropenem-EDTA Combined Disc Test (CDT). These isolates were further evaluated for their biofilm forming ability by the Microtitre Plate Method.Results: Out of 174 isolates, the species most frequently isolated was Acinetobacter calcoaceticus-baumannii complex (ACB) (89.1%). 70.1% isolates were resistant to Carbapenems, of which 45.1% were MHT positive and 73.8% were CDT positive. 63.7% of the isolates were biofilm producers.Conclusion: Simple identification schemes and antimicrobial susceptibility testing are cost effective and require fewer resources. Screening for Carbapenem resistance can help avoid unnecessary use of broad-spectrum antibiotics and thereby prevent treatment failure. Biofilms lead to decreased penetrability of antibiotics and make managing infections a clinical challenge. Further research is required to have a better understanding of the mechanism of biofilm formation and its implication in drug resistance.